Review: Women in plant disease management - Gullino, Maria Lodovica (Frontiers in Agronomy, 2023)
Women first began to take a stance in science over 50 years ago, and since then, they have produced a great number of publications. However, the first step towards science was a matter of accrediting women as rightful members of the scientific community. During the late nineteenth and early twentieth centuries, women started to enter into graduate programmes, and such a step helped them to make a difference. In many cases and many countries, botanists and mycologists were, in some way, pioneering in the plant pathology discipline. This manuscript considers some of the women who led the way in plant pathology, with a special focus on those who also dealt with the early aspects of plant disease management. Women who were active in different geographical areas are featured, and an attempt has also been made to provide some less well-known stories. Moreover, the importance of women behind the scenes, as is the case for many lab and field technicians, whose lives have not been chronicled, is acknowledged. Finally, some suggestions are given on how to improve the present situation and increase the number of women in science as well as in technical positions, with special emphasis on the positive effect of female mentors and role models.